Electric Current Aligning Component Units during Graphene Fiber Joule Heating. (23rd June 2021) - Cheng, Yi; Cui, Guang; Liu, Changhao; Liu, Zhetong; Yan, Longge; Liu, Bingyao; Yuan, Hao; Shi, Pengcheng; Jiang, Jun; Huang, Kewen; Wang, Kun; Cheng, Shuting; et al.
Abstract: Joule heating is featured with an extremely high rising rate of temperature with hundreds of kelvin per second, which has shown superiorities of high efficiency and energy conservation in graphene fabrication. Herein, we design a dynamic joule heating system for continuous synthesis of graphene fibers with ultrashort high‐temperature (≈2000 °C), treating time (≈20 min), and low electric energy consumption (≈2000 kJ m −1 ). During the joule heating fabrication, the current flowing through the fibers can manipulate the configuration of graphene sheets, the basic component units of fiber, and induce their alignment. Theoretical simulations reveal that graphene sheets tend to rotate towards the current direction under the current induced electric field for the highest stability with the lowest electric free energy and zero rotation torque. Therefore, the electrical and mechanical performances of as‐fabricated graphene fibers can be further improved in comparison with thermally annealed graphene fibers without applying current. Abstract : A dynamic joule heating system is designed, enabling the ultrafast and continuous fabrication of graphene fibers with a high‐temperature treating time of ≈20 min. Innovatively, the current‐induced electric field is first utilized to adjust the conformation order of graphene sheets and thus improves the electrical and mechanical properties of as‐fabricated graphene fibers.